2022
DOI: 10.1007/s10639-022-11121-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social education level on cybersecurity awareness and behaviour: a comparative study of university students and working graduates

Abstract: A multitude of studies have suggested potential factors that influence internet security awareness (ISA). Some, for example, used GDP and nationality to explain different ISA levels in other countries but yielded inconsistent results. This study proposed an extended knowledge-attitude-behaviour (KAB) model, which postulates an influence of the education level of society at large is a moderator to the relationship between knowledge and attitude. Using exposure to a full-time working environment as a proxy for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Hong et al [25] measured the impact of education level of great societies to moderate the correlation in the middle of knowledge and attitude by using the knowledge-attitudebehavior (KAB) model. Sabillon [26] introduced a model to evaluate the application and support of the cybersecurity awareness training model (CATRAM), constructed based on multiple case studies in Canadian higher education organizations.…”
Section: Motivation and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Hong et al [25] measured the impact of education level of great societies to moderate the correlation in the middle of knowledge and attitude by using the knowledge-attitudebehavior (KAB) model. Sabillon [26] introduced a model to evaluate the application and support of the cybersecurity awareness training model (CATRAM), constructed based on multiple case studies in Canadian higher education organizations.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…Physical and online students survey [25] Social education level on cybersecurity awareness and behavior They measure the impact of the education level of the great societies to moderate the correlation in the middle of knowledge and attitude by using the knowledge-attitude-behavior (KAB) model.…”
Section: Educationmentioning
confidence: 99%
“…According to the ndings of the preceding study, learners' attitudes toward cybersecurity would be in uenced by their internal education level and external environment, which would eventually change their internet behaviours. Furthermore, education level had a positive effect and work exposure time had a negative effect on a person's ISA [7,9].…”
Section: The In Uences Of Education Level and Sel On Isa In Chinamentioning
confidence: 98%
“…Although Parson et al [6] acknowledged in their initial HAIS-Q proposal that other social factors should be considered when using the KAB model or HAIS-Q in future research, there was no easy way to quantify social in uence. To adapt the framework, Hong et al [7] proposed an extended model of KAB (see Figure I), which suggested that more social contact at work implied a decrease in SEL.…”
Section: Hais-q and Extended Kab Modelmentioning
confidence: 99%
See 1 more Smart Citation